Gallery Walk Learning Model on Writing Exposition Texts - Anita Candra Dewi; Jenni Pannaco; Risnah; Juniarti Rara'Matande; Indrawati (International Journal of Sustainable Applied Sciences, 2024)
This study (1) examines how the Gallery Walk methodology helps class X students at SMA Negeri 1 Makassar write explanatory texts. (2) to evaluate the gallery walk model's effects on class X SMA Negeri 1 Makassar students' exposition writing activities and learning outcomes. The study is quasi-experimental. The study population is SMA Negeri 1 Makassar class X pupils. Study sample This sampled intentionally The designation is 52 person student. The experiment class has 34 students and the control class has 18. Research instruments These include interview instructions, sample observation sheets, student learning exercises, and tests. The Lilliefors test, Levene test, and independent sample t-test were employed to test data normality, homogeneity, and hypothesis. Hypothesis testing for student learning effectiveness yielded t counts > t tables (7.505 > 2.012) and significance 0.000 < 0.05, while student learning outcomes yielded t counts > t tables (6.699 > 2.012) and significance 0.000 < 0.05. Data shows that the gallery walk model improves writing exposition texts in class X pupils at SMA Negeri 1 Makassar better than the conventional model.